(untitled) (Revista Linhas, 2016)
This article reflects on the role textbooks have in the initial training of English teachers, which is based on the guidelines given by the traditional didactics that considers the textbook as an essential tool to teach a foreign language. Keywords: Textbook; English Teaching Training; Didactic Resources.